2014
DOI: 10.1177/1535370214549520
|View full text |Cite
|
Sign up to set email alerts
|

Comparative evaluation of N-acetylcysteine and N-acetylcysteineamide in acetaminophen-induced hepatotoxicity in human hepatoma HepaRG cells

Abstract: Acetaminophen (N-acetyl-p-aminophenol, APAP) is one of the most widely used over-the-counter antipyretic analgesic medications. Despite being safe at therapeutic doses, an accidental or intentional overdose can result in severe hepatotoxicity; a leading cause of drug-induced liver failure in the U.S. Depletion of glutathione (GSH) is implicated as an initiating event in APAP-induced toxicity. N-acetylcysteine (NAC), a GSH precursor, is the only currently approved antidote for an APAP overdose. Unfortunately, f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
26
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 72 publications
1
26
0
Order By: Relevance
“…This has been verified in previous studies, as well as its ability to chelate Cu 2+ , scavenge free-radicals, and protect against oxidative stress [29][30][31][32][33][34][35][36]. Our lab has demonstrated NACA's improved antioxidant ability compared to that of NAC [33,37]. Furthermore, NACA is effective at lower concentrations than NAC, which helps to prevent the various adverse effects that are associated with administration of higher doses of NAC [26,31,[38][39][40].…”
supporting
confidence: 77%
“…This has been verified in previous studies, as well as its ability to chelate Cu 2+ , scavenge free-radicals, and protect against oxidative stress [29][30][31][32][33][34][35][36]. Our lab has demonstrated NACA's improved antioxidant ability compared to that of NAC [33,37]. Furthermore, NACA is effective at lower concentrations than NAC, which helps to prevent the various adverse effects that are associated with administration of higher doses of NAC [26,31,[38][39][40].…”
supporting
confidence: 77%
“…On the other hand, our group showed previously that NAC attenuated the increase of oxidative stress in a neonatal pig model and reduced the levels of IL-1β [7]. Moreover, several investigators have displayed the many similar antioxidative effects of NAC and NACA [8,9]. …”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been revealed that NAC amide (NACA), an NAC derivate with higher bioavailability and enhanced antioxidant properties [8,9], may significantly mitigate the detrimental consequences of various toxic substances in different organs, including the lungs and kidneys [10,11,12]. …”
Section: Introductionmentioning
confidence: 99%
“…However, N-acetylcysteineamide's (NACA) characteristics as a drug were improved over NAC by neutralizing the carboxylic group of NAC, which makes the NACA molecule more lipophilic and, therefore, enhances its ability to penetrate cellular membranes (Grinberg et al, 2005). In addition, our own studies demonstrated that NACA is better than NAC in alleviating oxidative stress (Tobwala et al, 2013(Tobwala et al, , 2014. The enhanced ability to penetrate cells allows NACA to be administered at a lower dose than NAC, giving the drug a greater therapeutic index and lowering the risk of side effects that traditionally have been associated with higher doses of NAC (Cotgreave, 1997).…”
Section: Introductionmentioning
confidence: 97%